Successful outcome of six-level cervicothoracic corpectomy and circumferential reconstruction: case report and review of literature on multilevel cervicothoracic corpectomy - Acosta, Frank L. (Springer-Verlag, 2006)
The authors report the successful outcome of a six-level corpectomy across the cervico-thoracic spine with circumferential reconstruction in a patient with extensive osteomyelitis of the cervical and upper thoracic spine. To the authors’ knowledge, this is the first report of a corpectomy extending across six levels of the cervico-thoracic spine. Clinical relevance: the authors recommend anterior cage and plate-assisted reconstruction and additional posterior instrumentation using modern spinal surgical techniques and implants.